Use of healthcare consumer voices to increase empathy in nursing students. (March 2018) - Heidke, Penny; Howie, Virginia; Ferdous, Tabassum
Abstract: Nurses need to be well prepared to address the needs of a diverse population and facilitate positive experiences in an equitable and inclusive approach to care. The aim of the study was to determine whether the integration of consumer lived experience interviews into the content of a first-year course influenced empathy in nursing students. A one group pre-test, post-test design was used. A convenience sample of first-year undergraduate nursing students (N = 32) from a regional Australian university was recruited for the study. The pre and post tests were conducted using the Kiersma Chen Empathy Scale and t-tests performed to analyse the data. Results showed overall that nursing students demonstrated moderate levels of empathy; pre-test score of (M = 75.53; SD = 5.76). After the intervention the post-test results showed that there was a statistically significant increase in students' empathy towards vulnerable, disadvantaged and stigmatised population groups. The healthcare consumer voice has the potential to strengthen current teaching practices that promote caring behaviours in nursing students. Highlights: Empathy is a key component in therapeutic nurse-patient relationships. There were significant increases in students' empathy following intervention. Use of healthcare consumer voices in nursing curricula is worthwhile.